Hopelessness and social comparison in Turkish adolescent with visual impairment - ERGÜN, AYŞE; EROL, SAİME (WILEY, 2013)
The purpose of this study was to determine visually impaired adolescents' level of hopelessness and how they perceive of themselves socially compared to other individuals. Another purpose of this study was to look for relationships between hopelessness and social comparison in adolescents with visual impairment. The research population was comprised of 130 students at a secondary school for the visually impaired in Istanbul, Turkey. Our study demonstrated a weak relationship between social comparison and hopelessness (r=0.46, P < 0.000). The mean hopelessness score for the adolescents with visual impairment was 4.59 +/- 3.12 (girls: 4.23 +/- 3.10; boys: 4.83 +/- 3.11) and social comparison score was 87.50 +/- 11.19 (girls: 88.67 +/- 11.62; boys: 86.60 +/- 10.85). Hopelessness and social comparison were not affected by being blind from birth compared to later or from being a full-time boarding student compared to being a day student. The hopeless (Beck Hopelessness Scale score 9) adolescents' social comparison scores were found lower than hopeful ones' scores (P < 000). Factors affecting hopelessness and social comparison were feelings about their father, teacher and school.
Keywords: child and adolescent; hope and hopelessness; scales and assessment; schools; sociological issues; DEPRESSION; SCHOOL; UNIVERSITY; SYMPTOMS; SUPPORT